S.O.U.L: sing our unique lyrics! / Muhamad Ikhwan Mohd Zain and Aizu Hakimi Mohd Adnan - Mohd Zain, Muhamad Ikhwan; Mohd Adnan, Aizu Hakimi (2023)
Memorization of legal facts poses a challenge for students. The challenge stems from the dynamic and intricate nature of legal principles and regulations. In addition, the extensive volume of information that must be remembered contributes to the challenge students encounter when memorizing legal facts. Therefore, this study suggests a teaching design in which integrating music into the learning process can greatly improve information retention. Through the class activity named S.O.U.L., which stands for “Sing Our Unique Lyrics”, the impact of music on memory and cognitive function is revealed, revealing its potential as a valuable resource for law students. Students can enhance their ability to remember legal facts by linking them to melodies or rhythms. The goals of conducting this activity are to enhance creativity and productivity. By enabling students to create their own lyrics and melodies, they are encouraged to engage in unconventional thinking and express their individuality. Besides, it aims to enhance cognitive activity and enhance the pleasure of the learning experience. This activity also aims to enhance student engagement and facilitate better information retention. Implementing this activity offers many benefits as it stimulates various brain regions, enhancing students' ability to retain and retrieve essential information. Furthermore, the inherent rhythmic and melodic qualities of music contribute to the enhancement of the learning process, resulting in a more captivating and efficient approach to studying. In addition, presenting musical performances to peers can enhance self-assurance and proficiency in public speaking. The learning process may lead to potential commercialization, allowing students to showcase their talents and skills in performances or competitions. This may facilitate the promotion and distribution of their songs to a broader demographic, including law students and beyond. To conclude, this innovative approach of non-technological-based teaching and learning could have farreaching benefits for aspiring students around the world.